Run Code  | Code Wall  | Users  | Misc  | Feedback  | About  | Login  | Theme  | Privacy 

Math 9.5

Language: Editor: Layout:
+ ] Show input
Compilation time: 0,25 sec, absolute running time: 0,13 sec, cpu time: 0,09 sec, average memory usage: 16 Mb, average nr of threads: 3 
edit mode |  history  | discussion
\item \(-7x + 6y = -1 \\ 1x - 1y = -1\) @x = 7, y = 8
\item \(-1x - 1y = -3 \\ -3x + 2y = -4\) @x = 2, y = 1
\item \(2x - 4y = 2 \\ 2x - 5y = 5\) @x = -5, y = -3
\item \(-2x + 2y = 1 \\ 3x - 6y = 2\) @x = -5/3, y = -7/6
\item \(6x + 5y = -3 \\ -4x - 2y = 1\) @x = 1/8, y = -3/4
\item \(5x + 7y = 7 \\ -1x - 1y = -3\) @x = 7, y = -4
\item \(-6x + 7y = 3 \\ 2x - 3y = -2\) @x = 5/4, y = 3/2
\item \(7x + 5y = 1 \\ -2x - 1y = 1\) @x = -2, y = 3
\item \(-1x - 6y = 1 \\ 2x + 3y = -4\) @x = -7/3, y = 2/9
\item \(-6x + 6y = 2 \\ -6x + 5y = 3\) @x = -4/3, y = -1
\item \(-2x - 2y = -1 \\ 2x + 5y = -2\) @x = 3/2, y = -1
\item \(-6x + 5y = 2 \\ -6x + 4y = 1\) @x = 1/2, y = 1
\item \(2x + 2y = -3 \\ 3x + 4y = -8\) @x = 2, y = -7/2
\item \(2x - 3y = 1 \\ -3x + 4y = -3\) @x = 5, y = 3
\item \(-2x + 4y = -2 \\ 3x - 7y = 5\) @x = -3, y = -2
\item \(-2x - 2y = 4 \\ 1x + 4y = 1\) @x = -3, y = 1
\item \(-1x + 2y = -3 \\ 3x - 5y = 6\) @x = -3, y = -3
\item \(1x + 6y = 8 \\ 1x - 3y = 2\) @x = 4, y = 2/3
\item \(-3x + 4y = -5 \\ -6x + 6y = -8\) @x = 1/3, y = -1
\item \(-4x + 5y = -3 \\ -1x + 3y = -2\) @x = -1/7, y = -5/7
\item \(-6x - 7y = 5 \\ 5x + 7y = -3\) @x = -2, y = 1
\item \(2x - 1y = 3 \\ -4x + 3y = -2\) @x = 7/2, y = 4
\item \(1x - 1y = -2 \\ -5x + 8y = 7\) @x = -3, y = -1
\item \(-6x - 3y = -5 \\ -3x - 3y = -3\) @x = 2/3, y = 1/3
\item \(2x + 7y = 2 \\ 2x + 5y = -2\) @x = -6, y = 2
\item \(-4x + 3y = -2 \\ 1x - 1y = 1\) @x = -1, y = -2
\item \(4x - 3y = 2 \\ 5x - 3y = 1\) @x = -1, y = -2
\item \(-1x + 7y = -5 \\ 2x - 7y = 3\) @x = -2, y = -1
\item \(-3x + 2y = 1 \\ -2x - 1y = 2\) @x = -5/7, y = -4/7
\item \(-5x + 2y = -6 \\ -2x - 1y = -1\) @x = 8/9, y = -7/9
\item \(4x - 1y = 8 \\ 1x - 1y = 4\) @x = 4/3, y = -8/3
\item \(-2x - 4y = 7 \\ -1x - 5y = 5\) @x = -5/2, y = -1/2
\item \(-5x - 7y = -1 \\ 3x + 3y = -1\) @x = -5/3, y = 4/3
\item \(-4x - 6y = 3 \\ 1x + 2y = -2\) @x = 3, y = -5/2
\item \(-3x + 5y = -8 \\ 2x - 6y = 6\) @x = 9/4, y = -1/4
\item \(-6x + 4y = -1 \\ 5x - 3y = 2\) @x = 5/2, y = 7/2
\item \(-7x - 6y = -1 \\ -8x - 8y = -2\) @x = -1/2, y = 3/4
\item \(4x + 7y = -6 \\ -2x - 2y = 2\) @x = -1/3, y = -2/3
\item \(-3x + 7y = 8 \\ 2x - 7y = -4\) @x = -4, y = -4/7
\item \(-2x - 4y = -2 \\ 2x + 1y = 3\) @x = 5/3, y = -1/3
\item \(1x - 4y = 6 \\ -1x - 1y = 1\) @x = 2/5, y = -7/5
\item \(3x - 3y = -2 \\ 5x - 3y = -5\) @x = -3/2, y = -5/6
\item \(2x - 1y = 2 \\ 4x - 5y = 2\) @x = 4/3, y = 2/3
\item \(-1x + 7y = 8 \\ -1x + 5y = 6\) @x = -1, y = 1
\item \(-5x + 1y = -2 \\ 1x - 1y = 1\) @x = 1/4, y = -3/4
\item \(-1x - 1y = -1 \\ 2x - 1y = 8\) @x = 3, y = -2
\item \(1x + 4y = 1 \\ -1x + 2y = -7\) @x = 5, y = -1
\item \(7x - 6y = 2 \\ -8x + 6y = -1\) @x = -1, y = -3/2
\item \(-1x - 1y = -2 \\ 5x - 2y = 5\) @x = 9/7, y = 5/7
\item \(-1x - 3y = -1 \\ -1x + 3y = -4\) @x = 5/2, y = -1/2
\item \(1x + 2y = 2 \\ 1x + 1y = 3\) @x = 4, y = -1
\item \(-4x - 8y = -3 \\ -3x - 4y = -2\) @x = 1/2, y = 1/8
\item \(2x - 2y = 1 \\ 2x - 1y = 5\) @x = 9/2, y = 4
\item \(-3x + 3y = 4 \\ -1x - 2y = -1\) @x = -5/9, y = 7/9
\item \(2x - 1y = 2 \\ 1x + 2y = -2\) @x = 2/5, y = -6/5
\item \(-6x - 5y = -6 \\ -3x - 3y = -4\) @x = -2/3, y = 2
\item \(-1x - 6y = -6 \\ 2x + 4y = 3\) @x = -3/4, y = 9/8
\item \(1x - 3y = 4 \\ -1x - 3y = -3\) @x = 7/2, y = -1/6
\item \(-4x - 8y = -3 \\ 2x + 5y = 2\) @x = -1/4, y = 1/2
\item \(1x + 7y = 3 \\ 1x + 6y = 2\) @x = -4, y = 1
\item \(-3x + 4y = -8 \\ -4x + 5y = -8\) @x = -8, y = -8
\item \(4x + 4y = 3 \\ 1x + 2y = 1\) @x = 1/2, y = 1/4
\item \(-1x + 6y = -5 \\ 1x - 3y = 1\) @x = -3, y = -4/3
\item \(5x + 7y = -6 \\ 2x + 2y = -2\) @x = -1/2, y = -1/2
\item \(-5x + 7y = -3 \\ -1x + 1y = -1\) @x = 2, y = 1
\item \(2x - 1y = -5 \\ -4x + 3y = 7\) @x = -4, y = -3
\item \(1x - 8y = 1 \\ -1x - 1y = 2\) @x = -5/3, y = -1/3
\item \(-3x + 4y = 2 \\ 2x - 1y = -3\) @x = -2, y = -1
\item \(-1x - 2y = -2 \\ -3x - 4y = 2\) @x = -6, y = 4
\item \(-2x + 8y = -8 \\ -1x + 1y = -3\) @x = 8/3, y = -1/3
\item \(4x - 1y = -5 \\ 5x - 2y = -7\) @x = -1, y = 1
\item \(4x - 7y = -1 \\ 3x - 3y = -3\) @x = -2, y = -1
\item \(3x - 1y = 2 \\ 5x - 4y = 5\) @x = 3/7, y = -5/7
\item \(2x - 4y = 3 \\ -3x + 7y = -3\) @x = 9/2, y = 3/2
\item \(8x + 8y = 1 \\ 3x + 4y = 1\) @x = -1/2, y = 5/8
\item \(-4x + 4y = 1 \\ 6x - 7y = -3\) @x = 5/4, y = 3/2
\item \(-6x - 8y = -4 \\ 5x + 7y = 4\) @x = -2, y = 2
\item \(-1x - 3y = -3 \\ -2x - 2y = -8\) @x = 9/2, y = -1/2
\item \(3x - 3y = -5 \\ 4x - 2y = -8\) @x = -7/3, y = -2/3
\item \(2x - 2y = -2 \\ 2x - 1y = -6\) @x = -5, y = -4
\item \(1x - 3y = -1 \\ -4x + 8y = 2\) @x = 1/2, y = 1/2
\item \(-3x + 4y = 1 \\ -4x + 8y = 1\) @x = -1/2, y = -1/8
\item \(1x + 4y = -8 \\ 2x + 3y = -7\) @x = -4/5, y = -9/5
\item \(-3x - 2y = -1 \\ 5x + 2y = 4\) @x = 3/2, y = -7/4
\item \(-4x - 4y = -3 \\ 7x + 6y = 4\) @x = -1/2, y = 5/4
\item \(-1x + 4y = -1 \\ -3x + 4y = -7\) @x = 3, y = 1/2
\item \(1x - 6y = -5 \\ 2x - 4y = -8\) @x = -7/2, y = 1/4
\item \(-3x + 1y = -3 \\ 4x - 1y = 6\) @x = 3, y = 6
\item \(-4x - 3y = 8 \\ 2x + 3y = -6\) @x = -1, y = -4/3
\item \(-3x - 7y = 7 \\ -2x - 6y = 4\) @x = -7/2, y = 1/2
\item \(1x - 1y = 2 \\ -2x + 6y = -7\) @x = 5/4, y = -3/4
\item \(2x - 6y = -1 \\ -2x + 2y = 5\) @x = -7/2, y = -1
\item \(4x - 5y = -2 \\ -3x + 5y = 3\) @x = 1, y = 6/5
\item \(1x - 3y = -1 \\ -5x + 7y = -3\) @x = 2, y = 1
\item \(3x + 1y = -4 \\ -2x - 2y = 5\) @x = -3/4, y = -7/4
\item \(-2x + 2y = 3 \\ -5x + 4y = 5\) @x = 1, y = 5/2
\item \(-1x - 1y = -1 \\ 2x + 1y = 3\) @x = 2, y = -1
\item \(8x + 2y = 6 \\ 2x + 1y = 1\) @x = 1, y = -1
\item \(-1x - 4y = 4 \\ 1x - 4y = 1\) @x = -3/2, y = -5/8
\item \(-7x - 5y = 3 \\ -4x - 2y = 1\) @x = 1/6, y = -5/6